Kepercayaan Diri Peserta Didik Dari Status Sosial Ekonomi Rendah - Trisnawati, Wulan; Nurishlah, Laesti; Samadi, Mochammad Ramdan (MURABBI, 2024)
One of the problems that occurs among students from low socio-economic status is a lack of self-confidence, such as feeling inferior in social interactions with others, being embarrassed about being asked to appear in front of the class, being afraid of making mistakes and being ridiculed by friends, this can have an impact on psychological conditions. students in terms of interactions in everyday life. This research method uses literature studies with the aim of research to determine the extent of self-confidence of students from low socio-economic status. The research results show that low socio-economic status is not the main factor in students' lack of self-confidence with the existence of supporting factors such as the poor Student Assistance Program (BSM), individual counseling guidance and self-concept making the self-confidence of students from low socio-economic status equivalent to the self-confidence of students from high socioeconomic status.